Implementation of the Job Creation Law Number 11 of 2020 in the Welfare Sector in Tangerang Regency - Madhori; Amiludin; Ginanjar Suryatman, Arif; Fadli, Yusuf (Universitas Muhammadiyah Sidoarjo, 2023)
Worker welfare is a fulfillment of the needs and requirements required by workers, both facilities and services. In particular, this article aims not only to identify the implementation of Law number 11 of 2020 in Tangerang Regency, but also to analyze the welfare of workers after the implementation of the Job Creation Law and the efforts of the Manpower Department to ensure the welfare of workers in Tangerang Regency. Researchers used qualitative methods with a descriptive approach, the data used came from scientific articles, literature studies conducted before the research and interviews conducted through observation. The research results show that the implementation of the job creation law is still not underway, there are still companies that do not implement the law in accordance with the provisions of supervision from the government which is really needed. After the implementation of the Job Creation law there has been no immediate visible change, for the next 5 years there will be no increase in workers' wages. The Tangerang Regency Manpower Office carries out supervision in an effort to improve the welfare of workers so that they get the minimum wage, monitors working hours so that they comply with statutory regulations, and also ensures that workers receive BPJS Health.